High-level event: What science tells us about the impact of sustainable land use on reducing deforestation and building peace in Colombia - Villarino, Maria Eliza J. (CGIAR System Organization, 2022)
For the past four years, researchers from the Bioversity International Alliance and its partners, in the framework of the SLUS project funded by the International Climate Initiative of Germany, have been analyzing how sustainable land use, specifically organic agroforestry cocoa and silvopastoral systems, affect forest conservation trends and stability building in conflict-affected areas. The results of the research will be presented at the "Let's dialogue on sustainable land use systems for reducing deforestation and building peace" on December 13, 2022 in Bogota, Colombia.